Analiza zastosowań nowoczesnych technologii informacyjnych w bankowości spółdzielczej - Chmielarz, Witold (Application Analysis of Modern Information Technology in Co-Operative Banks, 2005)
The main goal of the paper is the status of information technology applications in co-operative banks identification. It is starting from a cooperative banking sector definition. Next - the role and place of IT in a co-operative banking is analyzing. In the end part of the work an attempt to comparative analysis of e-banking in this sector is undertaken.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1068, s. 30-37